PENGARUH KOMPETENSI DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI PUSAT PELATIHAN SUMBER DAYA MANUSIA (PPSDM) KEMENDIKDASMEN KOTA DEPOK - Riska Ainur Nikmah; Shela Indah Savitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effects of competence and job training on employee performance at the Human Resources Development Center (PPSDM) of the Ministry of Primary and Secondary Education in Depok City. The study used a quantitative associative approach. The population comprised 76 employees, all of whom were selected as respondents through saturated sampling. Data were collected using questionnaires and analyzed with SPSS version 27 through validity and reliability tests, classical assumption tests, simple and multiple linear regression, correlation, coefficient of determination, t-tests, and an F-test. Competence had a positive and significant effect on employee performance (t = 47.013; p < 0.001), while job training also had a positive and significant effect (t = 41.095; p < 0.001). Simultaneously, competence and job training significantly affected employee performance (F = 1285.321; p < 0.001). The multiple regression equation was Y = 1.544 + 0.602X1 + 0.354X2, with R² = 0.972, indicating that both variables explained 97.2% of the variation in employee performance.